Pengaruh ROA , ROE, Dan DER Terhadap Harga Saham Pada Perusahaan Perbankan Yang Terdaftar Di BEI - Nurhayati; Deny Yudiantoro (CV ODIS, 2022)
This study aims to examine the effect of ROA, ROE, and DER on stock prices in banking companies listed on the IDX for the 2017-2020 period. The population in this study is banking companies listed on the IDX. The samples in this study were 11 banking companies. This study uses a panel regression analysis method, which is processed using the e- views 10 programs. The coefficient of determination R2 shows that the ROA, ROE, and DER variables are able to influence stock prices by 21.3%. While the remaining 78.7% are leftover from other variables that are not used in. Partially ROA and ROE have a positive and significant effect on stock prices, DER has a negative and insignificant effect on prices. Simultaneously, the variables ROA, ROE, and DER affect stock prices.